A comprehensive sensorless control of DFIG-based wind turbines. Issue 1 (4th January 2016) - Abedinzadeh, Taher; Tohidi, Sajjad
Abstract : Purpose: – The purpose of this paper is to present an improved approach for estimation of the rotor position and speed of doubly fed induction generator, which can be used in vector control and direct torque control (DTC) schemes. Design/methodology/approach: – Some novel equations are developed for calculation of the rotor position and rotor speed. Such equations do not need to the value of stator flux linkage and just, measured values of the stator voltage and currents as well as rotor current are required to be known. Findings: – The simulation results verify the satisfactory steady-state and dynamic performance of proposed approach with both the vector control and DTC schemes. The results show that the proposed estimation approach benefits from the starting on the fly, robustness against the variations of the most of the stator and rotor parameters and immunity against the noise. Originality/value: – The proposed estimation approach is novel and the outcome of the research of authors. It is simple and effective and, no approximation is made in the calculations. The simulation results demonstrate that the proposed scheme can be successfully implemented in various control strategies, e.g. DTC and vector control.